Equation of state for a trapped quantum gas: remnant of zero-point energy effects - P C M Castilho; F J Poveda-Cuevas; J A Seman; R F Shiozaki; G Roati; S R Muniz; D V Magalhães; V S Bagnato (New Journal of Physics, 2016)
The study of the thermodynamic properties of trapped gases has attracted great attention during the last few years and can be used as a tool to characterize such clouds in the presence of other phenomena. Here, we obtain an equation of state for a harmonically trapped Bose–Einstein condensate taking the limit of $T→ 0$ by means of global themodynamic variables. These variables allow us to explore limits in which the standard thermodynamics are not defined. Our results are taken in the high density limit, and the extrapolation for $N→ 1$ is done later. Even in this situation, we qualitatively observe the well known existence of a zero-point energy for harmonic potentials in which the determination of conjugated variables is limited by the quantum nature of the system.